Marine debris and associated organic pollutants in surface waters of Chiloé in the Northern Chilean Patagonia (42°–44°S). (February 2023) - Ahrendt, C.; Galbán-Malagón, C.; Gómez, V.; Torres, M.; Mattar, C.; DeCoite, M.; Guida, Y.; Příbylová, P.; Pozo, K.
Abstract: We report the occurrence of plastics and associated persistent organic pollutants (POPs) in surface waters from Northern Chilean Patagonia. A total of 200 particles were found during the conducted survey. The highest number of particles found was 0.6 item m −3 . We found that 53 % of the collected particles corresponded to plastic, with an average of 0.19 ± 0.18 item m −3 . Microplastics (68 %) were the dominant size found in the area, followed by macroplastics (18 %) and mesoplastics (14 %). Most plastic particles were white (55 %) while others were <10 % each. Black and light blue represented 9 %; red, dark blue, and other colors 7 %; and green 6 %. Fragments were the most frequent shape of plastic debris (38 %), followed by Styrofoam (30 %) and fiber (27 %). Higher PBDE levels were found in the central zone, and those were higher than DDT, PeCB, HCB, and PCB levels. This study is the first report on POP occurrence in marine plastic debris from Chiloé Sea in the Northern Chilean Patagonia. Graphical abstract: Unlabelled Image Highlights: Surface marine debris from from Chilean Patagonia were analyzed in terms of size, color, type, composition, and associated POPs Up to 50 % of the collected particles were plastic with an abundance of 0.19 items m −3 in average. Polypropylene dominated the composition followed by polystyrene and polyethylene. POP contents on plastic debris was dominated by PBDEs followed by DDTs, PeCB, HCB and PCBs.